Penerapan Tutor Sebaya pada Pembelajaran Landasan Pendidikan Mahasiswa PGSD - Putri Indah Wahyuningsih; Nurjanah Sukmawati Sholekhatun Nisa (Elementary School and Education Journal, 2025)
Peer teaching is a learning strategy in which students who have a better understanding of the material help their peers who are having difficulty. The purpose of this article is to analyze the application of peer teaching in educational foundation learning. The peer teaching method can provide comfort to students because in general the relationship between friends is closer than the relationship between lecturers and students. The results of this study include the following aspects: 1) understanding of peer teaching all respondents already know and the benefits of peer teaching, 2) aspects of experience as a tutor, it was found that on average respondents had been tutors and had challenges in explaining the material to their friends, 3) Experience as a mentee that respondents have been mentees, with peer tutors having a positive impact on learning and, creating a pleasant learning atmosphere, more freedom and active in learning, 4) the results of peer teaching have an impact on more innovative learning and creating enjoyable learning, easy in understanding the material. The application of peer teaching in educational foundation learning has a positive impact starting from understanding the material, activeness in discussions and students are more able to explore their abilities in using learning methods.   Keywords: Peer Teaching, Educational Foundation, PGSD